CONOTAÇÕES MOSAICAS NO JESUS JOANINO: A RECEPÇÃO DAS TRADIÇÕES DE MOISÉS NA PERÍCOPE DE JOÃO 6.1-15 - SIQUEIRA, FELIPE BAGLI (2018)
The traditions of Moses, diffused by Judeo-Christian literatures (canonical and non-canonical texts) and present in the memory and popular orality of the first century, influenced the construction of the identity of several primitive Christian communities and interfered in the writing of texts guiding these communities in the New Testament period. In view of this, this research has as its object the relation between the image of Moses and the image of Jesus in the pericope of John 6: 1-15, starting from the hypothesis that this pericope is an indication that the process of writing the Gospel of John is part of this context, as we identify mosaic connotations in the Johannine Jesus. For this, we will use as a methodology, in a first moment, the bibliographical research, in order to understand some fundamental themes and concepts for the development of this research: the plurality of the Judeo-Christian movement; the Joanine Community and the drafting of the Gospel of John; the process of reception of religious traditions, memories and imaginaries; intertextuality and interdiscursivity; and the figure of Moses in the first century. Subsequently, we will make an exegetic-literary analysis of the pericope of John 6: 1-15 in an attempt to understand how the process of acquiring the imaginary of Moses in the Gospel of John is articulated as a key element in the construction of the image of the Johannine Jesus presented in the specified pericope. Therefore, this research hopes to understand the importance of this process of reception for the consolidation of the identity of the Joanine Community amid the conflicting plurality of the Judeo-Christian movement in the first century - taking into account the centrality of the figure of Moses in that environment. And, consequently, contribute to the studies of Early Christianity.